Analisis Pengaruh Number of Stages dan Banyak Pompa ESP di Sumur X - Saputri, Eriska Eklezia Dwi; Vani Nur Azizah (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
In well X, there has been a decline in oil production, leading to a decrease in the company’s revenue. This is due to an increase in the watercut percentage, as the reservoir itself operates on a water drive mechanism. Therefore, a follow-up action is needed to address this situation by using an artificial lift ESP with a tandem design. This approach aims to enhance the effectiveness and economic efficiency of the production process. The artificial lift Electrical Submersible Pump (ESP) used is a CENTRILIFT with model FC2700, series 400, installed at depths of 6371 ft and 6382 ft, respectively. A comparison of the two artificial lifts shows that the number of stages in the upper section is greater than in the lower section, resulting in a higher oil flow rate at the top, reaching 68.52 STB/d. Meanwhile, in the ESP well, oil flow rate has increased by 77.46 STB/d.